Impact of provincial competitiveness index (PCI) on economic development in the Red River Delta, Vietnam - Ngoc, Nguyen Thi Bao; Duy, Nguyen Vu (Jurnal Ekonomi & Studi Pembangunan, 2023)
The development of an economy is significant since it has far-reaching implications for several industries. Particularly, the income levels of inhabitants in crucial locations must reach a specific threshold for an economy to flourish effectively. To achieve this goal, it is vital to determine the factors that affect economic development. A significant aspect that can improve people's living standards is enhanced competitiveness. Therefore, this study employs the generalized ordinary least squares (GLS) method to examine the provincial competitiveness index (PCI) on economic development as measured by per capita income in the Red River Delta of Vietnam. The panel data of eleven Red River Delta provinces from 2010 to 2021 was studied. The results indicate that the provincial competitiveness index has a beneficial impact on economic growth and contributes to an increase in the income levels of the populace. The study also shows that labor literacy rate and trade openness also contribute to economic development while labor growth rate inhibits long-term economic development. Governments need to analyze indicators to find solutions to improve national competitiveness. In particular, it is necessary to pay attention to the business environment, apply technology in handling administrative procedures and have policies to support business capital creation for domestic enterprises.